The Effect of Interpersonal Communication Among Coworkers on the Mental Well–Being of Generation Z in Contemporary Work Settings - Irene Putri; Laurensius Reinald Diansilves Due; Daniel Deha; Khamoto Halawa; Ellyzabeth Siswardani (Jurnal Sosial Teknologi, 2026)
Generation Z now dominates Indonesia’s workforce and is known for valuing work–life balance and mental health. However, many companies face challenges such as work stress and high turnover among young employees. One key factor influencing this condition is the quality of coworker communication. This study aims to describe the quality of coworker communication, identify the mental health condition of Generation Z employees, and analyze the influence of coworker communication on mental health in modern workplaces. The research employed a quantitative approach through a closed-ended questionnaire (Likert scale 1–5) involving 70 Generation Z employees from various companies in Indonesia, complemented by qualitative semi-structured interviews to deepen understanding. Data were collected from October 2 to October 16, 2025, and analyzed using multiple linear regression with SPSS. The findings reveal a positive and significant influence of coworker communication quality on employees’ mental health, contributing 35% to the variation in mental health conditions. The novelty of this study lies in its specific focus on the relationship between coworker communication and mental health within Indonesia’s Generation Z workforce. The research implies that human resource management strategies should emphasize open communication, flexible work arrangements, and psychological support programs to improve the well-being of young employees.